The Effect of Carbon Dioxide Laser on Aphthous stomatitis Treatment: A Double-Blind Randomized Clinical Trial: Carbon Dioxide Laser and Aphthous stomatitis - Seyyedi, Seyyed Amir; Olyaee, Pooya; Fekrazad, Reza; Partovi, Sanaz; Baghizadeh Fini, Maryam (Journal of Lasers in Medical Sciences, 2020)
Introduction: This randomized clinical trial was designed to investigate the effect of carbon dioxide laser on the treatment of minor recurrent aphthous stomatitis (miRAS) as a painful and common oral ulcer. Methods: Fifteen patients with miRAS entered into this study after compliance with the inclusion and exclusion criteria. The patients were assigned to three groups of pulsed CO2 laser, continuous CO2 laser, and control. A pulsed CO2 laser with a power of 261 W and pulse duration of 180 microseconds and continuous CO2 lasers with the power of 1 W and radiation duration of 5-10 seconds were used. In the control group, topical triamcinolone ointment of 0.1% was used. The degree of pain was measured using the visual analogue scale (VAS). The patients were evaluated in terms of pain intensity before and immediately after the treatment and at follow-up hours, 12, 24, 48, and 72 hours after the intervention, and changes in the size of the ulcers were measured before the treatment and on third, fifth, and seventh days. Results: The effect of CO2 laser with pulsed and continuous radiation on the pain intensity of aphthous lesions, immediately after the treatment and at subsequent follow-up hours were similar and even better than the control group (P<0.05). All three treatments had a similar effect on the size of the ulcer, which was not statistically significant (P>0.05). Conclusion: The results of this randomized controlled trial (RCT) showed that the carbon dioxide laser, whether with pulsed radiation or continuous radiation compared to the control group, had a better impact on the pain relief of aphthous lesions.